Masques de Chine, visages du nuo : du patrimoine à l’art premier - Sylvie Beaud (Ateliers d'Anthropologie)
After their use had been prohibited for nearly two decades, Chinese masks, used mainly in rituals, made their reappearance in the public domain thanks to a relaxation of religious policy the 1980s. Cultural researchers and administrators then had the task of indexing and restoring them, necessitating the creation of a new administrative category. Resorting to an archaic term, Chinese masks their and connected practices were united under the term “nuo”, exorcism. The masks, collected by government officials after they were banned, made their way into Western private collections. The circulation of these artefacts led to changes in how they were handled, from their patrimonialisation to their “artification”, and also changed the usage of the term “nuo” itself. The present contribution aims to examine these different usages.